(untitled) (Psychology Travelogs, 2023)
The article examines the concept of psychotrauma, provides a theoretical analysis of the problem of researching psychotraumas in various reactions to the influence of psychogenic factors (factors), examines psychogenic factors and their influence on the psyche of military personnel. The purpose of the article is identification of regularities in the influence of psychotraumas in various reactions to the influence of psychogenic factors. The importance of the psychological study of the phenomenon of "psychotrauma", its psychological meaning and structure, its significance in changes in the state of mental and physical health of a person, is constantly noted by scientists from various branches of psychological science (general psychology, medical psychology, psychophysiology, engineering psychology, practical psychology, sports psychology, etc.), scientists of marginal and friendly fields of knowledge (medicine, valeology, pedagogy, physical education and debate, etc.). In domestic psychology, the study of the problem of "psychotrauma" is quite rare and has a scattered and fragmentary character. For the most part, this is due to known social reasons – conditions that reflect a person’s perception of the surrounding reality as threatening and unstable. Having examined in detail the current state of the study of the phenomenon «psychotrauma», its psychological content, we can come to the conclusion that today the state of society is characterized by an increased effect of factors that contribute to the mental traumatization of the individual and the reduction of the quality of life of a person. Such factors include: a relatively unstable political situation in the country and in the world, socio-economic uncertainty and anxiety, extreme life events (pandemic, war, migration). In our opinion, psychological trauma or psychotrauma is damage from the impact of negative factors on a person’s psyche, which can contribute to the development of mental illnesses. Often, the presence of psychological trauma can lead to a person needing treatment for PTSD. Psychotrauma can be associated with physical trauma that threatens a person’s life or violates the sense of security, which is accompanied by a strong emotional shock.